Reduction in blood product transfusion requirements with early on-ECMO repair of congenital diaphragmatic hernia - Stephen M. Niemiec; Amanda E. Louiselle; Ryan Phillips; Sarah A. Hilton; Sarkis C. Derderian; Michael V. Zaretsky; Henry L. Galan; Nicholas Behrendt; John P. Kinsella; Kenneth W. Liechty; Jason Gien (SpringerOpen, 2022)
Abstract Background For infants with severe congenital diaphragmatic hernia (CDH) stabilized with extracorporeal membrane oxygenation (ECMO), early repair on ECMO improves outcome; however when compared to operative repair after ECMO, repair on ECMO is associated with increase bleeding risk and need for blood product transfusions. Methods A retrospective review of 54 patients with CDH placed on ECMO prior to CDH repair was performed. For the subset of patients repaired on ECMO, analysis comparing those repaired early (within 48 h of cannulation) and late (beyond 48 h) on ECMO was performed. Outcomes of interest included survival to discharge, days on ECMO, and postoperative blood product utilization. Results When compared to those patients repaired prior to 48 h of ECMO initiation, 57.7% of patients survived versus 40.9% of late repair patients. For those repaired early, blood product utilization was significantly less. Early repair patients received a median of 72 mL/kg packed red blood cells (PRBC) and 75 mL/kg platelets compared to 151.9 mL/kg and 98.7 mL/kg, respectively (p < 0.05 respectively). There was no difference in median days on ECMO (p = 0.38). Conclusion Our data supports prior reports of improved outcome with repair with 48 h of ECMO initiation and suggests early repair on ECMO is associated with less bleeding and decreased blood product requirement in the postoperative period.